A nutrition strategy to reduce the burden of diet related disease: access to dietician services must complement population health approaches - Segal, Leonie; Opie, Rachelle S. (Frontiers in Pharmacology, 2015)
Poor diet quality is implicated in almost every disease and health issue. And yet, in most advanced market economies diet quality is poor, with a minority meeting guidelines for healthy eating. Poor diet is thus responsible for substantial disease burden. Societies have at their disposal a range of strategies to influence diet behaviors. These can be classified into; i) population level socio-educational approaches to enhance diet knowledge; ii) pricing incentives (subsidies on healthy foods, punitive taxes on unhealthy foods); iii) regulations to modify the food environment, and iv) the provision of clinical dietetic services. There is little evidence that societies are active in implementing the available strategies. Advertising of ‘junk foods’ is largely unchecked, contrasting with strict controls on advertising tobacco products, which also attract punitive taxes. Access to dieticians is restricted in most countries, even in the context of universal health care. In Australia in 2011 there were just 2,969 practicing dieticians/nutritionists or 1.3 clinicians per 10,000 persons, compared with 5.8 physiotherapists per 10,000 persons, 14.8 general practitioners (family physicians) per 10,000 persons or 75 nurses per 10,000 persons. Given the major role of diet in health it is time to implement comprehensive national nutrition strategies capable of effecting change. Such strategies need to be multi-component, incorporating both public health approaches and expanded publicly funded dietetic services. Access to individualized dietetic services is needed by those at risk, or with current chronic conditions, given the complexity of the diet message, the need for professional support for behavior change and to reflect individual circumstances. The adoption of a comprehensive nutrition strategy offers the promise of substantial improvement in diet quality, better health and wellbeing and lower health care costs.